Category structure and processing in 6‐year‐old children with autism. Issue 2 (12th July 2016) - Ellawadi, Allison Bean; Fein, Deborah; Naigles, Letitia R.
Abstract : This study investigated the categorization abilities of 6‐year‐old children with autism spectrum disorders (ASD) as compared to their peers with typical development (TD) using a category verification task. We examined the impact of stimulus typicality on multiple aspects of real‐time performance, including accuracy, reaction time, and performance stability. Both groups were more accurate in identifying typical category members than atypical ones; however, only the ASD group's accuracy was affected by item ordering, indicating less stable performance. Furthermore, category structure was predicted by concurrent language levels in the TD group but by concurrent nonverbal IQ in the ASD group; these latter two findings suggest that children with ASD process categories differently than their peers with TD. Autism Res 2017, 10: 327–336 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.